A genre analysis of letters of application written by students in Polytechnic Kuching Sarawak / Alfred Valentine Bakrin - Bakrin, Alfred Valentine (2009)
The study was carried out in Polytechnic Kuching Sarawak. The theoretical framework used in the study was adapted from earlier work by Swales (1990, 1991), Bhatia (1993) and Halliday (1994). The research analyzed the chosen genre (job application letters) from two possible angles; the linguistic features and the rhetorical features analysis. The linguistic features analysis focused on the politeness strategies that appeared in the mini-corpus. Under this analysis, the research focused on four elements that reflect politeness in a job application letter, namely; the salutation, the positive and negative politeness strategies and the complimentary close. The rhetorical features analysis, on the other hand, focused on the rhetorical moves and the rhetorical move sequences that appeared in the mini-corpus. The materials used in the research were letters of application produced by the students. 166 students were selected based on convenient sampling; therefore, the mini-corpus consisted of 166 letters produced by the students. The findings revealed interesting information within the scope of the research. Firstly, under the linguistic analysis, the results indicate although a significant number of students employed linguistic features such as salutation, and complimentary close, there are instances where they are used inappropriately. In addition, the students also included different rhetorical moves in their letters to enable them to achieve the communicative purpose of the letter. The results from the rhetorical features analysis indicate that there are eleven moves that appear in the mini-corpus. Moreover, results of the analysis indicate that even though the sequence of moves may differ from one job applicant to another, in general, there are certain moves patterns that are commonly shared by the students. It is important to note that genre analysis is not meant to replace other approaches but instead complement them by providing an alternative way in teaching and learning. It is hoped that teachers/lecturers, students, educators and anyone who has interest in the education field may benefit from reading this thesis.